Mohs Micrographic Surgery - what the gold standard in dermatologic surgery offers us. A Literature Review - Klaudia; Anna Kaźmierczak; Wiktoria Izdebska; Patrycja Sornek; Agata Borkowska; Anna Kiełb; Igor Pawlak; Anna Mich; Radosław Ciesielski; Jakub Stanek (Nicolaus Copernicus University in Toruń, 2024)
Introduction and objective: Micrographic Mohs surgery, a highly precise surgical technique, has long been regarded as a cornerstone in dermatology for the treatment of various skin cancers. This review aims to comprehensively summarize the current understanding of the principles and clinical applications of Mohs surgery, with a specific focus on providing insights to clinicians and researchers.   State of Knowledge: Mohs surgery is particularly renowned for its unparalleled efficacy in treating basal cell carcinoma (BCC), squamous cell carcinoma (SCC), and other skin malignancies, especially in anatomically challenging areas. The technique involves meticulous removal of cancerous tissue layers while sparing healthy surrounding tissue, facilitated by microscopic examination of surgical margins. Recent advancements in Mohs surgery have led to improved outcomes, with techniques such as immunostaining enhancing the accuracy of tumor detection and minimizing the need for additional surgeries.     Materials and methods: This review of studies is based on scientific articles avaible in PubMed, Google Scholar databases and Elsevier.   Summary: Micrographic Mohs surgery remains a cornerstone of dermatologic oncology, offering unparalleled precision and cure rates for various skin cancers. Its success lies in its ability to achieve complete tumor removal while preserving maximal tissue integrity and cosmesis. Future research endeavors should focus on refining surgical techniques, optimizing patient selection criteria, and exploring adjunctive therapies to further improve outcomes and patient satisfaction. By advancing our understanding and application of Mohs surgery, we can continue to provide optimal care for patients with skin cancer, ultimately improving their quality of life and prognosis.